Redes emergentes de comercialização agrícola em Sergipe - Santana, José Wagner Costa de (2014)
The study of emerging networks of agricultural marketing, in Sergipe, aims to analyze bases, structures, spatial configuration and contributions to agriculture challenges established by the expansion of the global economy which involves transformations of agriculture, driven by the dynamics of the internal and external markets. The analysis of emerging networks of agricultural marketing considers as fundamental elements the activities developed around the production and commercialization involving the countryside and the city, the family agriculture and market, the provision of technical-scientific-informational services, the network infrastructure that allows access to the markets of production and consumption, through actions that involve the presence of actors that constitute the system of networks installed amount and downstream of the primary production and processing of this production. To unveil the complexity that involves the various stages of marketing, was made wide bibliographical survey, being also conducted surveys of five-year census data, annual production and marketing, available in publications of national and international institutions and bodies, of representative institutions of classes. In addition, fieldwork was conducted, from visits to dozens of trade shows by sergipanas cities, to free capital markets and several commercial establishments of agricultural products and production processing. Interviews with professionals have been applied yet, managers, producers, intermediaries and consumers. This study focused on the sweet potatoes, milk, corn and poultry and eggs together in the last decade, are contributing to the dynamics of the contemporary economy and emerging marketing networks form. The expansion of these networks is enabling the access of small production developed by family farmers and agriculture the agricultural market shopping local, regional, national and global levels, seeking to monitor the dynamics of market agriculture operated by global integration of production and consumption. At the same time, the emerging agricultural marketing networks through its multiple forms, will be inserting in the competitive market through the agricultural access and adherence to formal and informal marketing dichotomous. Emerging networks are by crystallizing as occupying a prominent position in the economy and contribute significantly to changes in the landscape of Sergipe, forming new channels with streams of objects, things and linking capital markets, production and processing of internal and external consumption, increasing the visibility of the State as a producer, processor and exporter of consumer goods diversified.